Enhancing adolescent resilience to grief through ego state counseling - Ikhsan Hilmi; Mungin Eddy Wibowo; Sunawan Sunawan (SCHOULID: Indonesian Journal of School Counseling, 2024)
Grief is an inevitable part of the experience of losing a loved one, especially during adolescence. Research proves that grief is closely related to the level of resilience.  Individuals who have low resilience will have difficulty adapting to situations after being left by a loved one, thus having a negative impact on adolescents' lives. This study reports the findings of a study that used an A-B-A single case research design to analyze the effect of ego state counseling to enhance resilience with adolescent grief symptoms. Participants consisted of three junior high school students (N=3) who experienced grief symptoms and low levels of resilience. The ego state therapy intervention was delivered in 4 sessions. The treatment focused on emotional release, resolution, empowering, Commitment to change. Self-report data was collected at pre-, during, and post-ESC time points. Based on the results of Visual Analysis and statistical analysis using the Adolescent Resilience Scale (ARS) and Prolonged Grief Disorder (PG-13-Revised) instruments, it was revealed that students who participated in ego state counseling experienced a significant decrease in sadness and an increase in resilience during the counseling process and after four weeks post-ESC. This evidence shows ego state counseling in improving resilience in adolescents with grief. For further research, it is possible to expand the research subjects with a variety of different backgrounds